Optimalisasi Penentuan Bonus Karyawan dengan Sistem Pendukung Keputusan Metode TOPSIS di PT. Elizabeth Hanjaya - Asia, Siti Nur; Fuad, M Noor; Saleh, Husna; As'ad, Muhammad; Irfan, Irfan (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
PT. Elizabeth Hanjaya is a retail company that provides various fashion products, PT. Elizabeth Hanjaya is a retail company that offers a variety of fashion products such as bags, shoes, accessories, and fashion supplies for men and women. This study uses the Technique for Order Performance by Similarity to Ideal Solution (TOPSIS) method to build a decision support system in determining employee bonus recipients in this company. The purpose of the study is to design a system that can assess the feasibility of receiving employee bonuses based on the TOPSIS method. This method works by choosing an alternative that has the closest distance from the positive ideal solution and the furthest from the negative ideal solution based on geometric principles. The system is designed using Unified Modeling Language (UML) and developed with the PHP programming language. The results of the study show that the assessment system is able to produce accurate decisions. Based on testing with four alternatives, the TOPSIS method determines alternative 1 as the employee who is most eligible to receive a bonus with a final value of 0.675360. In addition, user evaluation results showed a high level of satisfaction, with 92% of respondents giving a "strongly agree" rating.